A systemic, multidimensional and territorialized framework for assessing the adaptation potential of sustainable agrifood transitions: theoretical guidelines and exploratory insights from the metropolitan region of Chile - Marco Billi; Marco Billi; Valentina Barrera; José Navea; Constanza Jiménez; Romina Cáceres; Sebastián Palma (Frontiers in Sustainable Food Systems)
IntroductionThe urgency of responding to climate change poses new challenges for agrifood systems, both to make them more sustainable and neutral in terms of greenhouse gas emissions, meet carbon neutrality commitments, and promote their adaptation to a changing climate, while also promoting territorial resilience. In this context, fostering the transformation of traditional agriculture toward innovative models that promote the development and adoption of innovative and ecologically sustainable and resilient adaptation measures, mechanisms and processes becomes extremely urgent. Growing interest has been emerging around approaches and experiences to develop and assess barriers and opportunities for ‘sustainable’ agrifood transitions (‘SAT’). Despite these developments, there is still a lack of an integrated and territorialized analytical framework to account for the potential of SAT to respond to the risks and challenges associated with climate change. In view of this, this paper proposes an analytical framework that hopes to integrate the previous advances around a robust, systemic, multisectoral and context-sensitive observation of the potential of SAT as a strategy to address climate change risks.MethodsThis framework articulates around four complementary analytical lenses: the ‘risk’ lens addresses the ‘potential’ need for adaptation (why do we need SAT?); the ‘resilience’ lens focuses on how SAT may reduce risk (what do SAT do?); the third, ‘sociotechnical transitions’, looks at potential opportunities and barriers for the adoption and scaling up of these practices (how can SAT occur?); finally, the socio-technical “imaginaries” lens sheds light on the perceptions, expectations and visions behind the SAT (what are they for?). These analytical frameworks will be exemplified through incipient research that applies these observation lenses with the Metropolitan Region of Santiago de Chile as a case study.Results and discussionThis exploratory approach allows to illustrate the observation framework and generating initial hypotheses about the territory under study. This favors a more holistic and systemic view of food security and the different elements that can generate risks to it, or promote its resilience, from a systemic and territorial approach, helping to understand why the SAT are necessary and how they can become potential strategies to promote food security in a context of climate change.